Strand 4: Stockton-on-Line (Sol) - a Case Study - McGoldrick, Theresa; Shelley, Viv; Cummins, Pat (Proceedings of the International Conference on Networked Learning, 1998)
The partnership "Stockton-on-Line" (SoL) was established in 1997 between University College Stockton (University of Durham), the Borough of Stockton-on-Tees Education Department, Stockton and Billingham College of Further Education, on Demand Information plc and Comcast Business Solutions. The aim of the project, as expressed in the bid for ERDF funding was follows- "to widen participation in adult, further and higher education by students who traditionally do not participate in education beyond school age. Particular target groups are people in socio-economic classes D, E and C2. The MORI adult education survey (I 994) has shown that 70% of people in socio-economic class DE and 56% of people in socio-economic class C2 have not engaged in education since leaving school. Young unemployed men between the ages of 18-25 and women returners are also considered to be important users of the project." Stockton-on-Line aims to be the major source of distributed education, training and related information and learning services for the whole community in Stockton-on-Tees. The project represents a real and unique example of cross-sectoral collaboration in lifelong learning in a dynamic and fast-changing environment where partners have genuine difficulties of interest to resolve, particularly where their understanding of their own traditional learner markets are concerned. This paper will develop a case study of the project from inception to the point at which the first teaching materials are to be delivered by the system.